The role of the law in the institutionalization of industrial conflict with specific reference to the use of the lock-out in South Africa - De Witt, Charl Cilliers (Department of Commercial Law, 2024)
Difference of opinion exists as to whether the law has a role to play in the institutionalization of industrial conflict. It is argued in this thesis that it does. Firstly, the thesis deals with the development of an institutionalization model allowing for an effective and legitimate role for the law, particularly with regard to the regulation of managerial industrial power in the overall institutionalization design. It is argued that the law has a procedural role to play in the regulation of the quantum of industrial power, the nature of disputes which should be settled by the use of power and the position of power as a last resort in the overall institutionalization design. Secondly, the thesis addresses the use of managerial power in the South African industrial relations system against the background of the above model. It starts off with an evaluation of contract as a means to regulate employment and it is concluded that contract fails to address the power discrepancies between capital and labour on both an economic and hierarchical level and it further fails to provide security of employment. The unfair labour practice concept designed to redress the inadequacies of contract was fairly successful in the area of security of employment, but failed in the area of collective bargaining. The legislature should codify the law with regard to security of employment and restrict the ambit of the unfair labour practice to collective bargaining. The latter should be regulated in terms of clear, procedural, legislative provisions. After an analysis of the institutionalization design of the South African system the regulation of the lock-out itself is evaluated with regard to the size of managerial power, the kind of disputes it is designed to settl·e and the position of the lock-out vis-a-vis other settlement mechanisms in the overall institutionalization design. Finally, suggestions with regard to the definition of certain key concepts are made.